ANALISIS ULANG STABILITAS LERENG BENDUNGAN TUKUL PACITAN AKIBAT CLIMATE CHANGE - Arintha Indah Dwi Syafiarti; Mohamad Ferdaus Noor Aulady; Laras Laila Lestari; Dyan Eka Nurhayati; Biantoro Pambudi (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
This aim of this study is to evaluate the impact of climate change on the hydrological, hydraulic, and slope stability conditions of the Tukul Dam in the Kali Telu watershed, Pacitan. The methodology includes hydrological analysis using the Log Pearson Type III distribution, flood discharge estimation with the HSS Nakayasu method, and hydraulic simulation using HEC-RAS to determine maximum floodwater elevation. Slope stability was analyzed with Geostudio using the Bishop method to determine the factor of safety (FS). The results indicate that the maximum 1,000-year rainfall reaches 550.82 mm, generating a peak discharge of 1,152.26 m³/s, exceeding the design discharge of 380.73 m³/s. Hydraulic simulation showed a floodwater elevation of +183.59 meters, while slope stability analysis confirmed that all FS values remained above the safe limit of 1.30, ensuring dam stability. This study integrates updated hydrological data with geotechnical modeling to enhance understanding of dam resilience under extreme conditions. Recommendations include spillway capacity improvements, early warning systems, and continuous monitoring to mitigate future flood risks.